Isolation and Characterization of a Diesel-degrading Bacterium from Waters Near the Langkawi UNESCO Kilim Karst Geoforest Park (Bulletin of Environmental Science and Sustainable Management (e-ISSN 2716-5353), 2023)
This study explored the biodegradation potential of bacterial isolates from various locations in Malaysia, focusing on their ability to utilize diesel as a carbon source. Among the ten isolates tested, Isolate 4, identified as Pseudomonas sp. strain UPM-Langkawi 3 based on morphological, cultural, and biochemical properties, exhibited significant growth on 2.5% diesel, indicating rapid activation of diesel assimilation mechanisms. Using ABIS online software analysis, the strain was provisionally identified as Pseudomonas sp. UPM-Langkawi 3. Experimental results demonstrated that the optimal conditions for the growth of strain UPM-Langkawi 3 were between 6 and 8 % (v/v) diesel concentration, a temperature of between 28 and 35 °C, and a pH range of between 7.5 to 8.5. The strain showed inhibited growth at higher diesel concentrations and temperatures above 40°C and at a lower pH of 5.7. Among several inorganic nitrogen sources tested, 0.9% w/v ammonium sulphate was found to be the most effective, corroborating previous research. The study underscores the efficacy of Pseudomonas sp. strain UPM-Langkawi 3 in degrading diesel, suggesting its potential use in bioremediation of diesel-contaminated environments. Further research should employ molecular identification techniques, such as 16srRNA gene sequencing, to confirm the species identity and optimize biodegradation conditions. This work establishes a foundation for utilizing indigenous bacterial strains in environmental management strategies, particularly for areas impacted by hydrocarbon pollutants.
Keywords: Isolation; Characterization; Diesel-degrading; Pseudomonas sp.; Langkawi UNESCO site